(untitled) (Medical Forum Monthly, 2020)
Objective: To comparison between antibiotic therapy and appendectomy in patients presented with uncomplicated acute appendicitis. Study Design: Randomized controlled trial Place and Duration of Study: This study was conducted at the Department of Surgery Bacha Khan Medical Complex Swabi from March 2019 to February 2020. Materials and Methods: One hundred and thirty patients of both genders presented with uncomplicated acute appendicitis were included and divided all the patients equally into two groups A and B. Each group comprised 65 patients. Group A received appendectomy while group B received antibiotic treatment. Outcomes such as hospital stay, complications, recurrence within one year and patient’s satisfaction were examined. Results: There were 40 (61.54%) male and 25 (38.46%) female patients in group A with mean age 30.06±8.72 years while in group B 36 (55.38%) male and 29 (44.62%) were females with mean age 29.42±9.65years. Significant difference was observed regarding hospital stay between group A and B (2.02±0.85 days Vs 6.28±2.44 days) p-value 0.001. Regarding complications group B had overall lower rate of complications as compared to group A [(2 (3.08%) Vs 10 (15.38%)] a significant difference was observed between both group (p=0.02). In group A 1 (1.54%) patient develop recurrence while in group B 16 (27.69%) developed recurrence within 1 year. In group A 63 (96.92%) patients were satisfied while in group B 44 (67.69%) patients were satisfied with treatment modality. Conclusion: Surgical treatment is safe and effective treatment modality with higher patients satisfaction and successful treatment rate as compare to antibiotics treatment.